Designing the Organization Development Model with Organizational Agility Approach in the Department of Education in Sistan and Baluchistan Province - Fatemeh Heydari Amin; Farideh Hashemiannejad; Nazia Sadat Nasseri (Iranian Evolutionary Educational Psychology Journal)
Objective: The aim of this research was to formulate an organizational development model from the perspective of organizational agility within the General Department of Education in Sistan and Baluchistan province. Methods: This study employed a mixed exploratory design, specifically a sequential exploratory mixed research design, encompassing both qualitative and quantitative phases. In the qualitative phase, the study focused on individuals with university education, experts, opinion leaders, professors, elites within the scientific community, and specialists, who were purposefully selected (totaling 25 participants). In the quantitative phase, the research considered managers and employees of the General Department of Education in Sistan and Baluchistan province (comprising 681 individuals). In the qualitative phase, the Delphi method was employed, while the quantitative section utilized structural equation modeling to investigate the central research question and align the model with the collected data. Results: The outcomes of the research revealed that the organizational development consisted of four dimensions: professional development, organizational development, individual development, and educational development. Moreover, the organizational agility model identified four dimensions: responsiveness, flexibility, change management, and performance enhancement. In conclusion, this research underscores the importance of developing a human resource strategy aligned with organizational strategies, fostering a shared vision, promoting intellectual synergy, welcoming innovative ideas, and instilling a culture of systemic thinking regarding organizational development among members of the organization. Conclusions: These measures are essential steps toward creating a more agile organization, as recommended for managers and officials.